Endoscopically resected duodenal lipoma as an uncommon cause of upper gastrointestinal bleeding: a case report - Dong Chan Joo; Gwang Ha Kim; Bong Eun Lee; Moon Won Lee; Cheolung Kim (The Ewha Medical Journal)
Subepithelial tumors in the upper gastrointestinal (GI) tract are often detected during nationwide endoscopic gastric cancer screening in Korea. Most GI lipomas are asymptomatic and do not necessitate further treatment. However, large tumors may lead to complications such as bowel obstruction, intussusception, and bleeding. These GI lipomas require endoscopic or surgical resection. On radiological examination, GI lipomas typically manifest as hypodense lesions with similar density to that of fat tissue. White-light endoscopy generally reveals a yellowish subepithelial tumor exhibiting a positive cushion sign, while endoscopic ultrasonography shows a homogeneous hypoechoic mass within the third layer of the GI tract. We present the case of an 81-year-old woman with symptomatic duodenal lipoma following endoscopic resection.